Phylogeography of reef fishes across the line Islands: uncovering population structure in a data deficient region - Mackenzie Woods; Brian J. Zgliczynski; Stuart A. Sandin; Dakota Betz; Ronald S. Burton (Marine Biology, 2025)
Despite decades of study, it remains difficult to predict the genetic structure of populations of marine species, even with extensive knowledge of the regional oceanography, geography, and the life history of the species. Genetic data provide key insights into population structure that cannot be otherwise inferred. To this end, phylogeographic patterns across the Line Islands were assessed in three unrelated species of reef-associated fish, Stegastes aureus , Lutjanus bohar , and Pseudanthias bartlettorum using the mitochondrial gene cytochrome oxidase I (COI). All three species show evidence of significant population differentiation, with the sharpest break separating the southernmost islands of Vostok and Millennium from the islands to the north. This pattern is broadly consistent with results of larval dispersal simulations based on available ocean current data and estimated planktonic dispersal durations for the three species. Bayesian generalized linear modeling shows correlation between geographic distance and genetic distance for L. bohar and P. bartlettorum but was unable to find a significant predictor variable for differentiation in S. aureus . While the presence of differentiated fish populations within the Line Islands is clearly demonstrated, the reasons for the apparent phylogeographic break near the southern end of the archipelago remain unclear.

Tracking data highlight the importance of human-induced mortality for large migratory birds at a flyway scale - Juan Serratosa; Steffen Oppel; Shay Rotics; Andrea Santangeli; Stuart H.M. Butchart; Luis S. Cano-Alonso; Jose Luis Tellería; Ryno Kemp; Aaron Nicholas; Aigars Kalvāns; Aitor Galarza; Aldina M.A. Franco; et al. (Biological Conservation, 2024)

Extensive regional variation in the phenology of insects and their response to temperature across N orth A merica - Peter O. Dunn; Insiyaa Ahmed; Elise Armstrong; Natasha Barlow; Malcolm A. Barnard; Marc Bélisle; Thomas J. Benson; Lisha L. Berzins; Chloe K. Boynton; T. Anders Brown; Melissa Cady; Kyle Cameron; et al. (Ecology, 2023)
Climate change models often assume similar responses to temperatures across the range of a species, but local adaptation or phenotypic plasticity can lead plants and animals to respond differently to temperature in different parts of their range. To date, there have been few tests of this assumption at the scale of continents, so it is unclear if this is a large‐scale problem. Here, we examined the assumption that insect taxa show similar responses to temperature at 96 sites in grassy habitats across North America. We sampled insects with Malaise traps during 2019–2021 ( N = 1041 samples) and examined the biomass of insects in relation to temperature and time of season. Our samples mostly contained Diptera (33%), Lepidoptera (19%), Hymenoptera (18%), and Coleoptera (10%). We found strong regional differences in the phenology of insects and their response to temperature, even within the same taxonomic group, habitat type, and time of season. For example, the biomass of nematoceran flies increased across the season in the central part of the continent, but it only showed a small increase in the Northeast and a seasonal decline in the Southeast and West. At a smaller scale, insect biomass at different traps operating on the same days was correlated up to ~75 km apart. Large‐scale geographic and phenological variation in insect biomass and abundance has not been studied well, and it is a major source of controversy in previous analyses of insect declines that have aggregated studies from different locations and time periods. Our study illustrates that large‐scale predictions about changes in insect populations, and their causes, will need to incorporate regional and taxonomic differences in the response to temperature.

An integrated approach to assessing abiotic and biotic threats to post‐fire plant species recovery: Lessons from the 2019–2020 Australian fire season - Rachael V. Gallagher; Stuart P. Allen; Berin D. E. Mackenzie; David A. Keith; Rachael H. Nolan; Libby Rumpff; Carl R. Gosper; Geoffrey Pegg; Stephen van Leeuwen; Mark K. J. Ooi; Colin J. Yates; Cory Merow; et al. (Global Ecology and Biogeography, 2022)
Aim Existing abiotic and biotic threats to plant species (e.g., disease, drought, invasive species) affect their capacity to recover post‐fire. We use a new, globally applicable framework to assess the vulnerability of 26,062 Australian plant species to a suite of active threats after the 2019–2020 fires. Location Australia. Time period 2019–2020. Major species studied Plants. Methods Spatial data for existing threats and information on species‐level susceptibility were combined with estimates of the extent of range burnt in southern Australia (> 22°S) to assign species against 10 criteria into vulnerability categories ( high , medium , low , none , data deficient ). We explore in detail results for three threats (drought, disease, feral animals), highlighting where impacts from multiple threats ranked high vulnerability may compound to reduce post‐fire recovery. Results Analysis of the full suite of 10 vulnerability criteria, which encompass a broad range of threats, revealed large numbers of species vulnerable to poor post‐fire recovery from one or more different hazards ( high vulnerability: 1,243 species; medium vulnerability: 2,450 species). Collectively, 457 plant species that burnt extensively (> 50%) across their range are highly vulnerable to poor recovery due to exposure to pre‐fire drought conditions (235 species), disease (186 species), or feral animals (97 species). Of these 457 species, 61 are vulnerable to more than one of these three threats, highlighting how a suite of interacting hazards can impact plant recovery after fire. Main conclusions While fire can renew plant populations by stimulating recruitment and resetting competitive interactions, the presence of existing threats in post‐fire landscapes jeopardizes recovery. The simultaneous impact of multiple threats that impact recovery can create a suite of hazards that contribute to declines and, potentially, extinction. Our method for rapid post‐fire vulnerability assessment can be applied to large numbers of plant species or other biota in fire affected regions globally.

Fire‐related threats and transformational change in Australian ecosystems - David A. Keith; Stuart P. Allen; Rachael V. Gallagher; Berin D. E. Mackenzie; Tony D. Auld; Sarah Barrett; Anne Buchan; Valerie English; Carl Gosper; Dave Kelly; Allen McIllwee; Rachel T. Melrose; et al. (Global Ecology and Biogeography, 2022)
Aim Megafire events generate immediate concern for wildlife and human well‐being, but their broader ecological impacts likely extend beyond individual species and single fire events. In the first mechanistic study of fire effects focussed on ecosystems, we aimed to assess the sensitivity and exposure of ecosystems to multiple fire‐related threats, placing impacts in the context of changing fire regimes and their interactions with other threats. Location Southern and eastern Australia. Time period 2019–2020. Major species studied Australian ecosystems. Methods We defined 15 fire‐related threats to ecosystems based on mechanisms associated with: (a) direct effects of fire regime components; (b) interactions between fire and physical environmental processes; (c) effects of fire on biological interactions; and (d) interactions between fire and human activity. We estimated the sensitivity and exposure of a sample of 92 ecosystem types to each threat type based on published relationships and spatial analysis of the 2019–2020 fires. Results Twenty‐nine ecosystem types assessed had more than half of their distribution exposed to one or more threat types, and only three of those were listed as nationally threatened. Three fire‐related threat types posed the most severe threats to large numbers of ecosystem types: high frequency fire; pre‐fire drought; and post‐fire invasive predator activity. The ecosystem types most affected ranged from rain forests to peatlands, and included some, such as sclerophyllous eucalypt forests and heathlands, that are traditionally regarded as fire‐prone and fire‐adapted. Main conclusions Most impacts of the 2019–2020 fires on ecosystems became apparent only when they were placed in the context of the whole fire regime and its interactions with other threatening processes, and were not direct consequences of the megafire event itself. Our mechanistic approach enables ecosystem‐specific management responses for the most threatened ecosystem types to be targeted at underlying causes of degradation and decline.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

A boreal songbird's 20,000 km migration across North America and the Atlantic Ocean - William V. DeLuca; Bradley K. Woodworth; Stuart A. Mackenzie; Amy E. M. Newman; Hilary A. Cooke; Laura M. Phillips; Nikole E. Freeman; Alex O. Sutton; Lila Tauzer; Carol McIntyre; Iain J. Stenhouse; Scott Weidensaul; et al. (Ecology, 2019)

A field test of the effects of body composition analysis by quantitative magnetic resonance on songbird stopover behaviour - Lisa V. Kennedy; Yolanda E. Morbey; Stuart A. Mackenzie; Philip D. Taylor; Christopher G. Guglielmo (Journal of Ornithology, 2017)

Variation in songbird migratory behavior offers clues about adaptability to environmental change - Anna M. Calvert; Stuart A. Mackenzie; Joanna Mills Flemming; Philip D. Taylor; Sandra J. Walde (Oecologia, 2012)

Genetic Typing of Classical Swine Fever Viruses from Lao PDR by Analysis of the 5′ Non-Coding Region - Stuart D. Blacksell; Syseng Khounsy; David B. Boyle; Laurence J. Gleeson; Harvey A. Westbury; John S. Mackenzie (Virus Genes, 2005)